Integrating rural landscape design and sustainable development: a comprehensive framework for ecological preservation and resource management - Qiu, Wen (Archives of Civil Engineering, 2026)
Rural landscape design and sustainable development are deeply interconnected, requiring a multifaceted approach that involves scientific design principles, effective resource management, and the active participation of diverse stakeholders. This paper provides a comprehensive examination of the relationship between rural landscape design and sustainable development, focusing on the integration of ecological preservation with sustainable resource utilization. Through a detailed analysis of theoretical foundations, current challenges, and strategic design interventions, this research highlights the socio-economic benefits that arise from well planned rural landscapes, including improved aesthetics, enhanced biodiversity, and increased resource efficiency. The findings emphasize the necessity of balancing environmental conservation with human activity to foster long-term rural resilience and sustainability. This study offers a valuable framework for policymakers, designers, and researchers, supporting future efforts to implement sustainable practices in rural landscape design. By advancing practical strategies and theoretical insights, this research contributes to the development of sustainable rural environments that harmonize ecological health with socio-economic growth, ensuring a sustainable future for rural communities.